Case Report on Colloidal Nodular Goiter - Sharma, Bindu; Sexena, Reteka (Homœopathic Links, 2019)
Goiter refers to an enlarged thyroid gland which can be caused by a number of factors such as biosynthetic defects, iodine deficiency, autoimmune disease and nodular diseases. A case of a woman with colloidal nodular goiter treated successfully with Homoeopathy is reported here. Her thyroid profile was within normal range, and fine-needle aspiration cytology was clearly suggestive of colloidal nodular goiter. She was treated with homoeopathic medicines following holistic concepts of homoeopathy, and the result was significant reduction in size of thyroid nodule. Lycopodium initiated the action, and Sulphur potentiated the cure.
Keywords: colloidal; goiter; homoeopathy; neck swelling